2021
DOI: 10.1261/rna.079025.121
|View full text |Cite
|
Sign up to set email alerts
|

Release of the ribosome biogenesis factor Bud23 from small subunit precursors in yeast

Abstract: Ribosomes are the universally conserved ribonucleoprotein complexes that synthesize proteins. The two subunits of the eukaryotic ribosome are produced through a quasi-independent assembly-line-like pathway involving the hierarchical actions of numerous trans-acting biogenesis factors and the incorporation of ribosomal proteins. The factors work together to shape the nascent subunits through a series of intermediate states into their functional architectures. The earliest intermediate of the small subunit (SSU … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Release of U3 snoRNA and binding of Bud23 are both required for the binding of Rps2 (uS5), Rps0 (uS2), and Rps21 (eS21). Consistently, the absence of Bud23 impairs pre-40S nuclear export, leading to reduced production of mature 40S subunits ( White et al, 2008 ) and a severe growth defect, which can be suppressed by weakly binding mutants of these AFs and overexpression of Rps2 ( Black et al, 2020 ; Black and Johnson, 2022 ). Binding of Rps2, Rps0, and Rps21 in turn is required for Bud23 release ( Black and Johnson, 2022 ) promoted by the kinase Rio2, which then takes the position of Bud23 ( Black and Johnson, 2022 ; Linnemann et al, 2019 ).…”
Section: Ribosome Assembly At a Glancementioning
confidence: 88%
See 2 more Smart Citations
“…Release of U3 snoRNA and binding of Bud23 are both required for the binding of Rps2 (uS5), Rps0 (uS2), and Rps21 (eS21). Consistently, the absence of Bud23 impairs pre-40S nuclear export, leading to reduced production of mature 40S subunits ( White et al, 2008 ) and a severe growth defect, which can be suppressed by weakly binding mutants of these AFs and overexpression of Rps2 ( Black et al, 2020 ; Black and Johnson, 2022 ). Binding of Rps2, Rps0, and Rps21 in turn is required for Bud23 release ( Black and Johnson, 2022 ) promoted by the kinase Rio2, which then takes the position of Bud23 ( Black and Johnson, 2022 ; Linnemann et al, 2019 ).…”
Section: Ribosome Assembly At a Glancementioning
confidence: 88%
“…Consistently, the absence of Bud23 impairs pre-40S nuclear export, leading to reduced production of mature 40S subunits ( White et al, 2008 ) and a severe growth defect, which can be suppressed by weakly binding mutants of these AFs and overexpression of Rps2 ( Black et al, 2020 ; Black and Johnson, 2022 ). Binding of Rps2, Rps0, and Rps21 in turn is required for Bud23 release ( Black and Johnson, 2022 ) promoted by the kinase Rio2, which then takes the position of Bud23 ( Black and Johnson, 2022 ; Linnemann et al, 2019 ). Surprisingly, even though Rio2, Rps2, Rps0, and Rps21 promote Bud23 release in a partially reconstituted system ( Black and Johnson, 2022 ), Rio2 binding is independent of these RPs ( Linnemann et al, 2019 ; Black and Johnson, 2022 ).…”
Section: Ribosome Assembly At a Glancementioning
confidence: 88%
See 1 more Smart Citation
“…To gain more insights into functional interrelationships between r-protein assembly and pre-rRNA folding events, we analysed here the impact of the assembly of the S0-cluster of r-proteins on the pre-rRNA fold and the general architecture of late nucleoplasmic to early cytoplasmic yeast SSU precursors. Previous biochemical studies indicated that S0-cluster formation is required for the production and accumulation of yeast SSUs [33,[40][41][42][43][44][45]. Effects were observed on the dynamics of their nuclear export, the cytoplasmic release of the ITS1, the recruitment of factors such as Nob1, and the release of other factors such as Slx9, Rrp12, and Bud23.…”
Section: Introductionmentioning
confidence: 99%
“…RpS21 is component of the small subunit of the ribosome with functions in translation initiation and ribosome biogenesis ( Török et al 1999 ; Sato et al 2003 ; Tabb-Massey et al 2003 ; Black and Johnson 2022 ). In Drosophila , haploinsufficient RpS21 mutants exhibit the classic Minute phenotype of short and thin bristles, prolonged development, and impaired viability ( Török et al 1999 ; Marygold et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%